2023
DOI: 10.33423/jhetp.v23i2.5810
|View full text |Cite
|
Sign up to set email alerts
|

Development of Reading Literacy Assessment Questions: An Effort to Improve Students’ Critical Thinking

Abstract: This study aims to (1) conduct needs analysis, (2) design literacy assessment questions, (3) validate literacy assessment questions, (4) test literacy assessment questions, (5) examine the validity and reliability of literacy assessment questions, and ( 6) analyze literacy assessment questions. This research employed a survey, need analysis, problem design, validation questions, revision questions, test questions, validity and reliability tests of questions, and item analysis of questions. The results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The developed of dHOTLearn model based on PLW model has been validated by 3 experts. The expert validation carried out is useful to know systematically whether the developed dHOTLearn is in accordance with the objectives or not (Nurhayati et al, 2023). The eligibility data by media experts was obtained through content and construct validity, then media experts provided assessments, suggestions and comments on the available instruments (Bekbayeva et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The developed of dHOTLearn model based on PLW model has been validated by 3 experts. The expert validation carried out is useful to know systematically whether the developed dHOTLearn is in accordance with the objectives or not (Nurhayati et al, 2023). The eligibility data by media experts was obtained through content and construct validity, then media experts provided assessments, suggestions and comments on the available instruments (Bekbayeva et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Research by Nurhayati uncovered that the students' and teachers' needs analysis results indicated they did not comprehensively understand the reading literacy questions. In addition, the teachers could not design and organize reading literacy questions (Nurhayati et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Proficient reading literacy skills enable people to extract meaning from text, fostering knowledge development and participation at national and international levels (OECD, 2019). Thus, reading literacy assessment includes questions about critical thinking, while reading literacy activities demand higher-order cognitive skills (Nurhayati et al, 2023). Modern research highlights reading literacy as a pivotal competency in contemporary society, drawing increasing attention (Lan & Yu, 2023).…”
Section: Reading Literacy Assessmentmentioning
confidence: 99%